Adipose-derived mesenchymal stem cells from infrapatellar fat pad of patients with rheumatoid arthritis and osteoarthritis have comparable immunomodulatory properties. (17th February 2016) - Skalska, Urszula; Kontny, Ewa
Abstract: Adipose-derived mesenchymal stem cells (ASCs) possess immunosuppressive properties, but their activity is dependent on stimuli provided by local environment. It is possible that proinflammatory milieu of rheumatoid joint affects ASCs function. To verify this hypothesis, rheumatoid ASCs (RA-ASCs) and osteoarthritic ASCs (OA-ASCs) derived from infrapatellar fat pad (IPFP) of the knee joint have been compared. RA- and OA-ASCs isolated from patients were cultured in vitro . Their secretory and proliferative activity was measured. Peripheral blood mononuclear cells (PBMCs) from healthy donors were co-cultured with ASCs. Then, PBMCs proliferation was measured by 3 H-thymidine incorporation method, cytokines secretion by immunoassays, T cells activation and regulatory T cells (Tregs) percentage – by flow cytometry. RA- and OA-ASCs properties in vitro were comparable, however, some differences in secretory activity occurred. RA- and OA-ASCs inhibited PBMCs proliferation and induced interleukin 10 production but up-regulated interleukin 17 A secretion and failed to limit release of other proinflammatory mediators (tumor necrosis factor [TNF], interferon γ [IFNγ], CCL5) by PBMCs. RA- and OA-ASCs did not suppress activation markers expression on T cells and did not trigger Tregs expansion. The present study shows that IPFP-ASCs from RA and OA patients have comparable functions in vitro . Their immunosuppressive activity seems to be impaired comparing to available data.